Assessing the Impact of COVID-19 on the Management of Students with Hearing Impairment: A Case of Selected Secondary Schools in the Northern Education Division - Kabuye, Emmanuel (Mzuzu University, 2024)
COVID-19 pandemic had negatively affected the education system in many countries and it was worse to students with disabilities which includes those students with hearing impairment. The purpose of this study was to assess the impact of COVID-19 on the school support for students with hearing impairment (A case of selected secondary schools in the Northern Education Division). The study was guided by the following specific objectives: (i) explored the impact of COVID-19 on the management of students with hearing impairment; (ii) examined how school managements are implementing inclusive education with emphasis on students with hearing impairments in the COVID-19 situation; (iii) explored interventions that could be made to better support implementation of inclusive education during Pandemics especially for students with hearing impairment. The study was informed by the interpretivist paradigm as it posits that social reality is subjective and it advocates for multiple reality and viewpoints from the lived experiences of participants. The study was conducted in Mzimba District in the Northern Education Division (NED). Data was collected from three secondary schools on the basis that they all practice inclusive education. Twenty-six participants were purposively selected and they included the NED Education Division Managers, School Managers, Teachers, Parents and Students. These participants were selected on the basis that they know how students including those with hearing impairment were impacted by COVID-19. . Data was analysed thematically, and findings revealed that management of students with hearing impairment was negatively affected by COVID-19 due to several factors such as an abrupt holiday that came into play,the introduction of online lessons left students with hearing impairment behind, and measures that were developed to reduce the spread of the disease also negatively affected the v schooling of these students. The study recommends that the curriculum be reviewed to make it robust enough to always remain truly inclusive and withstand pandemics such as COVID-19. Proper policies have to be put in place for the education system to better respond to pandemics and ensure continuity of education provision including developing teaching and learning resources that support inclusive education. Lastly, teachers have to be oriented on how best to ensure continuity of inclusive education even during pandemics.
Keywords: Person with disabilties; Pandemic; Outbreak